2019
DOI: 10.7554/elife.47209
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced endocannabinoid signaling mediated by sigma-1 receptors and extracellular vesicle secretion

Abstract: Cocaine is an addictive drug that acts in brain reward areas. Recent evidence suggests that cocaine stimulates synthesis of the endocannabinoid 2-arachidonoylglycerol (2-AG) in midbrain, increasing dopamine neuron activity via disinhibition. Although a mechanism for cocaine-stimulated 2-AG synthesis is known, our understanding of 2-AG release is limited. In NG108 cells and mouse midbrain tissue, we find that 2-AG is localized in non-synaptic extracellular vesicles (EVs) that are secreted in the presence of coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…Previous studies have shown that stimulants alter the biogenesis and release of multiple EV subtypes, which in turn may affect cell‐to‐cell communication, and play a role in addiction (Carone et al., 2015; Meng et al., 2020; Nazari et al., 2018). In the mouse VTA, cocaine stimulate the release of EVs that modulate synaptic transmission (Nakamura et al., 2019), an established component to DA neuron plasticity and consequent drug dependency and craving (Kauer & Malenka, 2007). Cocaine also stimulates the release of CD63+ EVs in the mouse VTA, which is dependent on alpha‐synuclein (α‐Syn) (Trubetckaia et al., 2019), a protein that is increased in both the blood and brain of humans that use cocaine and is correlated with increased drug craving (Mash et al., 2008; Qin, Ouyang, Pablo, & Mash, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that stimulants alter the biogenesis and release of multiple EV subtypes, which in turn may affect cell‐to‐cell communication, and play a role in addiction (Carone et al., 2015; Meng et al., 2020; Nazari et al., 2018). In the mouse VTA, cocaine stimulate the release of EVs that modulate synaptic transmission (Nakamura et al., 2019), an established component to DA neuron plasticity and consequent drug dependency and craving (Kauer & Malenka, 2007). Cocaine also stimulates the release of CD63+ EVs in the mouse VTA, which is dependent on alpha‐synuclein (α‐Syn) (Trubetckaia et al., 2019), a protein that is increased in both the blood and brain of humans that use cocaine and is correlated with increased drug craving (Mash et al., 2008; Qin, Ouyang, Pablo, & Mash, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs in circulating biofluids are located within extracellular vesicles (EVs) or bound to protein/lipoprotein particles, and they function in cell‐to‐cell communication. Recent studies in cultured cells, rodent models, and humans have begun to examine the effect of stimulants, including MA, cocaine and tobacco on EV biogenesis and release from cells (Carone et al., 2015; Cordazzo et al., 2014; Enjeti, Ariyarajah, D'crus, Seldon, & Lincz, 2017; Nakamura et al., 2019; Nazari, Zahmatkesh, Mortaz, & Hosseinzadeh, 2018; Serban et al., 2016; Trubetckaia, Lane, Qian, Zhou, & Lane, 2019). In regards to MA, plasma endothelial‐derived EVs have been shown to be increased in MA treated rats (Nazari et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At this VTA synapse, NE engages postsynaptically-expressed a 1 -ARs to promote DA neuron output, suggesting that NE signaling may serve an overall disinhibitory role on mesolimbic circuit activity (Wang et al, 2015). Furthermore, COC application elicits an a-AR-dependent depression in synaptic strength that is occluded by NET blockade (Wang et al, 2015;Nakamura et al, 2019). One plausible explanation for these differences is that each monoamine system possesses distinct release dynamics (e.g., levels of tonic activity, neurotransmitter clearance, etc.).…”
Section: Ne Selectively Regulates Glutamatergic Transmission Onto Pv-insmentioning
confidence: 99%
“…Closely related to METH in terms of prevalence of use and mechanism of action, cocaine is one of the most prolifically abused stimulants. Recently, cocaine has been shown to stimulate EV release through the sigma-1 receptor (Sig-1R)-ARF6 (ADP-ribosylation factor 6) complex [113]. Further, Nakamura et al showed that the interactions among Sig1-Rs, cocaine, and EVs may regulate synaptic transmission in the brain through the release of 2-AG (2-arachidonoylglycerol; an endocannabinoid that is increasingly synthesized with cocaine stimulation); this release of 2-AG contributes to the inhibition of GABAergic input to dopamine neurons [113].…”
Section: Cocainementioning
confidence: 99%
“…Recently, cocaine has been shown to stimulate EV release through the sigma-1 receptor (Sig-1R)-ARF6 (ADP-ribosylation factor 6) complex [113]. Further, Nakamura et al showed that the interactions among Sig1-Rs, cocaine, and EVs may regulate synaptic transmission in the brain through the release of 2-AG (2-arachidonoylglycerol; an endocannabinoid that is increasingly synthesized with cocaine stimulation); this release of 2-AG contributes to the inhibition of GABAergic input to dopamine neurons [113]. Interestingly, in a glioblastoma culture model, cocaine exposure not only increased EV release but also increased tunneling nanotubule (TNT) formation [114][115][116]; both EVs and TNTs are highly correlated with the development of many diseases, such as glioblastoma and neurodegenerative diseases [117,118].…”
Section: Cocainementioning
confidence: 99%